Serum 25‐hydroxyvitamin D concentrations in dogs with coccidioidomycosis and variables associated with extent of clinically evident disease. (11th January 2023) - Jaffey, Jared A.; Kreisler, Rachael; Shubitz, Lisa F.; Backus, Robert C.; Hostnik, Eric T.; Wycislo, Kathryn L.; Monasky, Ross; Schaffer, Magen; Holland, Cyndi
Abstract: Background: Clinicopathologic variables predictive of disseminated coccidioidomycosis are known in humans but have not been explored in dogs. Serum 25‐hydroxyvitamin (OH)D correlates with severity of disease of various etiologies in dogs but its role in coccidioidomycosis is unknown. Objective: Determine whether serum 25(OH)D concentrations are different in dogs with coccidioidomycosis compared with healthy controls and if clinicopathologic variables are associated with extent of disease. Animals: Thirty‐five dogs with coccidioidomycosis (pulmonary, n = 13; disseminated, n = 15; uncharacterized, n = 7), and 25 healthy control dogs. Methods: Prospective cohort study. Serum 25(OH)D and C‐reactive protein (CRP) concentrations were measured with modified‐HPLC and a commercial ELISA kit, respectively. Results: There was no difference in 25(OH)D concentrations between dogs with coccidioidomycosis (median, interquartile range [IQR]; 31.9 ng/mL, 23.3‐49.2) and controls (29.5 ng/mL, 25.6‐40.8, P  = .73). Serum 25(OH)D concentration was lower in dogs with coccidioidomycosis and IgG titers ≥1:32 than dogs with titers below this cut‐off ( P  = .02). Dogs with IgG titers ≥1:32 were more likely to have disseminated disease (OR, 7.5; 95% CI: 1.1‐68; P  = .03). Serum CRP concentrations were higher in dogs with IgG titers ≥1:16 (median, IQR; 4474.8 ng/mL, 2885.8‐8236.1) than in those below this cut‐off (151.2 ng/mL, 30.4‐2907.3; P  = .02). There was a significant inverse association between serum 25(OH)D and CRP at 25(OH)D concentrations ≤33 ng/mL. Conclusion and Clinical Importance: Serum 25(OH)D concentration was lower for dogs with IgG titers ≥1:32, indicating a potential association between semi‐quantitative titers and 25(OH)D concentrations in dogs with coccidioidomycosis. IgG titers ≥1:32 yielded higher odds of disseminated disease, but was inadequate as a standalone test to determine form of disease.